High risk of complications after a "low risk" procedure: A national study of nursing home residents and older adults undergoing haemorrhoid surgery. (23rd September 2022) - Colley, Alexis; Finlayson, Emily; Zhao, Shoujun; Boscardin, John; Suskind, Anne
Abstract: Aim: To evaluate 30‐day complications and 1‐year mortality for older adults undergoing haemorrhoid surgery. Method: This retrospective cohort study evaluated older adults (age 66+) undergoing haemorrhoid surgery using Medicare claims and the minimum data set (MDS). Long‐stay nursing home residents were identified, and propensity score matched to community‐dwelling older adults. Generalized estimating equation models were created to determine the adjusted relative risk of 30‐day complications, length of stay (LOS), and 1‐year mortality. Among nursing home residents, functional and cognitive status were evaluated using the MDS‐activities of daily living (ADL) score and the Brief Instrument of Mental Status. Faecal continence status was evaluated among a subset of nursing home residents. Results: A total of 3664 subjects underwent haemorrhoid surgery and were included in the analyses. Nursing home residents were at significantly higher risk for 30‐day complications (52.3% vs. 32.9%, aRR 1.6 [95% CI: 1.5–1.7], p < 0.001), and 1‐year mortality (24.9% vs. 16.1%, aRR 1.6 [95% CI: 1.3–1.8], p < 0.001). Functional and mental status showed an inflection point of decline around the time of the procedure, which did not recover to the baseline trajectory in the following year. Additionally, a subset of nursing home residents demonstrated worsening faecal incontinence. Conclusion: This study demonstrated high rates of 30‐day complications and 1‐year mortality among all older adults (yet significantly worse among nursing home residents). Ultimately, primary care providers and surgeons should carefully weigh the potential harms of haemorrhoid surgery in older adults living in a nursing home.